A new railway tunnel under Brussels? Assessing political feasibility and desirability with competence-based multi criteria analysis. (August 2018) - te Boveldt, Geert; Van Raemdonck, Koen; Macharis, Cathy
Abstract: Interjurisdictional infrastructure planning is a complex affair due to the multiplicity of actors representing the jurisdictions, sometimes at several institutional levels. Their priorities are likely to conflict, as the ratio between costs and benefits of infrastructure differs according to place and to scale. Yet, for evaluating strategic decisions, policy makers typically use methods that assess impacts from a single-actor viewpoint, providing little insight in the political feasibility and desirability of projects that cross institutional borders. This paper presents a novel evaluation and group decision-making framework: Competence-based Multi Criteria Analysis (COMCA). It provides a structure for applying Multi Criteria Decision Analysis-based methods in a multi-actor, multi-level context. The framework can be used to evaluate the desirability of project alternatives for each of the actors, whose support, individually or as a group, is deemed necessary. Doing so, COMCA helps mapping local and global interests, providing valuable insight and input into the interjurisdictional decision-making and negotiation process. The article describes how COMCA was applied in a study with the aim to assess solutions for the main bottleneck of the Belgian railway network. It was found that, in terms of desirability among stakeholders, certain little-studied alternatives potentially surpass the alternatives which for many years were regarded as the most plausible options by the key players. Based on experiences during the study, the article discusses various parameters for finding the equilibrium between methodical precision and applicability in a real-world decision-making context. Highlights: A novel framework is presented for applying Multi Criteria Decision Analysis in a multi-actor multi-level context. It is especially suited for cross-border transport projects, as the cost-benefit ratio of a project varies according to place and to scale, which complicates decision making. The desirability of project alternatives is assessed for each actor individually and for each group of actors with equivalent roles in the project. Providing an overview of global and local desirability, it also provides an indication of political feasibility. The article discusses its application in a study on the main bottleneck in the Belgian railway network.